A case of esophageal rupture caused by long-term exposure to vinegar and resolved by damage control strategies. Issue 10 (21st October 2020) - Okura, Tomohiro; Inaba, Mototaka; Yasuhara, Isao; Kataoka, Masafumi
Abstract: A 75-year-old woman had the habit of drinking vinegar. She had emergent transport to our hospital because of vomiting and unconsciousness. The patient underwent emergency surgery for esophageal rupture and septic shock. Intraoperatively, a 25 mm perforated area was found, and the visible esophageal mucosa was black. Because the suture closure or anastomosis was difficult and the shock was prolonged, she was placed in the intensive care unit after undergoing resection of the thoracic esophagus and thoracic drainage. Fifteen hours after the first surgery, we performed external esophagostomy and enterostomy. The third surgery was a retrothoracic cervical esophagogastric anastomosis, and reconstructive surgery was performed 60 days after the first surgery. Prolonged exposure to vinegar may have resulted in esophageal mucosal necrosis. This is a valuable case in which the esophageal mucosa was necrotic, and we performed esophagectomy and reconstruction as a damage control strategy to save her life.